Ubiquitin-modifying enzymes in Huntington’s disease - Sap, Karen A.; Geijtenbeek, Karlijne W.; Schipper-Krom, Sabine; Guler, Arzu Tugce; Reits, Eric A. (Frontiers in Molecular Biosciences, 2023)
Huntington’s disease (HD) is a neurodegenerative disorder caused by a CAG repeat expansion in the N-terminus of the HTT gene. The CAG repeat expansion translates into a polyglutamine expansion in the mutant HTT (mHTT) protein, resulting in intracellular aggregation and neurotoxicity. Lowering the mHTT protein by reducing synthesis or improving degradation would delay or prevent the onset of HD, and the Ubiquitin-Proteasome-System (UPS) could be an important pathway to clear the mHTT proteins prior to aggregation. The UPS is not impaired in HD, and proteasomes can degrade mHTT entirely when HTT is targeted for degradation. However, the mHTT protein is differently ubiquitinated when compared to wild-type HTT (wtHTT), suggesting that the polyQ expansion affects interaction with (de)ubiquitinating enzymes and subsequent targeting for degradation. The soluble mHTT protein is associated with several ubiquitin-modifying enzymes, and various ubiquitin-modifying enzymes have been identified that are linked to Huntington’s disease, either by improving mHTT turnover or affecting overall homeostasis. Here we describe their potential mechanism of action toward improved mHTT targeting towards the proteostasis machinery.